The dynamics of venture capital contracts - Carsten Bienz; Julia Hirsch (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We analyze the degree of contract completeness with respect to staging of venture capital investments using a hand-collected German data set of contract data from 464 rounds into 290 entrepreneurial firms. We distinguish three forms of staging (pure milestone financing, pure round financing and mixes). Thereby, contract completeness reduces when going from pure milestone financing via mixes to pure round financing. We show that the decision for a specific form of staging is determined by the expected distribution of bargaining power between the contracting parties when new funding becomes necessary and the predictability of the development process. To be more precise, parties choose the more complete contracts the lower the entrepreneur's expected bargaining power - the maximum level depending on the predictability of the development process.
urn:nbn:de:hebis:30-26076
Keywords: G24; G32; D86; D80; G34; 330; Venture Capital; Corporate Governance; Moral Hazard; Renegotiation; Contract Theory; Empirical Contract Theory; Contract Econometrics